Resource Governance: Corporate Structure and Risk Management For Chinese Investments in Indonesia's Coal and Nickel Sectors Under Indonesian Law - Adilla Meytiara Intan (Green Publisher Indonesia, 2026)
This study aims to analyze the legal and regulatory framework governing Chinese investments in Indonesia’s coal and nickel sectors, focusing on corporate structure requirements and risk management strategies under Indonesian law. Based on the formulation and evaluation of a transdermal gel using Bajakah Tampala (Spatholobus littoralis Hassk.) extract as an anti-inflammatory agent, the study concluded that the formulation produced a stable transdermal gel in the form of a film, with a yield of 19.4% from 500 grams of plant material. The gel has a brown color, a characteristic Bajakah odor, and forms a dry, crack-free film. Patch weights ranged from 0.107 to 0.192 g, with a thickness of 0.11–0.16 mm, and the gel withstood more than 400 foldings without damage. The formulation utilized HPMC as a gelling agent, propylene glycol as a humectant, and Tween 60 as an enhancer, producing a gel suitable for transdermal application. Physical evaluations showed that all formulas had a pH within the skin’s physiological range (5.2–6.2), ensuring safety for topical use. Organoleptic evaluation confirmed dry, crack-free films with smooth surfaces. Viscosity and homogeneity supported consistent active-ingredient release, while uniform patch weights ensured stable dose distribution. Formulas with enhancers (F2 and F3) exhibited better physicochemical properties, particularly in terms of pH stability and weight consistency. In vivo tests on rats induced with a 1% carrageenan solution showed varying anti-inflammatory effects: Formula F1 reduced edema by 0.13 ml, while F2 (0.30 ml) and F3 (0.31 ml) were more effective, approaching the positive control (diclofenac sodium, 0.45 ml).